Development of an in-vehicle power line communication network with in-situ instrumented smart cells - Timothy A. Vincent (Elsevier, 2021)
Instrumented cells, equipped with miniature sensors, are proposed to aid the next stage of electrification in the automotive and aerospace industries. To optimize the energy density available within a lithium ion (li-ion) pack we demonstrate how a power line communication (PLC) network can be formed at an individual cell level. This reduces the need for complex communication cables within a vehicle wiring loom.Here we show a unique prototype smart cell (instrumented cell equipped with interface circuitry and processing capability) can be connected via a PLC network, to enable monitoring of vital parameters (temperature, voltage, current), regardless of cell state of charge (2.5 V to 4.2 V DC operating voltage). In this proof-of-concept study, we show the reliable system (0 errors detected over ∼24 hr experiment, acquired data (logged at 10 Hz) from cells (in a parallel configuration), and comparative data for cell internal and external temperature was recorded. During a prolonged discharge (1C, 5A discharge) a peak core temperature >3 °C hotter than surface temperature was observed, highlighting the need to understand cell operation in cooling system design.